Japan in war and peace : - W. Dower, John
Japan's racism, rooted in pride in the purity and homogeneity of its society, has remained constant from the feudal era to the present and is potentially dangerous to its relations with the rest of the world, according to Dower, who is Henry Luce professor of international cooperation and global stability at MIT. In this collection of powerful, evenhanded and crystalline essays, he tracks manifestations of racism in the nation's mythology, cinema, wartime behavior and adaptations to the postwar occupation. He analyzes the nature of Japanese capitalism, the nation's emergence as a world power, its politicians and its government. Dower examines the Japanese sense of superiority to the mongrelized U.S. population as a factor in trade problems, but he also argues that the U.S.'s own sense of superiority and enduring contempt for the "little yellow devils" still underly our fear and awe of the Japanese. He punctures manipulated postwar myths in both Japan and the U.S. of a frail, kindly Hirohito and reviews General Douglas MacArthur's dealings with him. Dower warns of new dangers: that Japan's extreme conservatives will continue to "sanitize the 'holy war' waged in the emperor's name," that they will remilitarize and that "the cult of Japanese uniqueness can stimulate highly irrational nationalistic emotions." Illustrations.